Supporting evidence for PCB pollution threatening global killer whale population - Schnitzler, Joseph G.; Reckendorf, Anja; Pinzone, Marianna; Autenrieth, Marijke; Tiedemann, Ralph (Prof. Dr.); Covaci, Adrian; Malarvannan, Govindan; Ruser, Andreas; Das, Krishna; Siebert, Ursula (Aquatic Toxicology, 2018)
A recent Science report predicted the global killer whale population to collapse due to PCB pollution. Here we present empirical evidence, which supports and extends the reports’ statement. In 2016, a neonate male killer whale stranded on the German island of Sylt. Neonatal attributes indicated an age of at least 3 days. The stomach contained ∼20 mL milk residue and no pathologies explaining the cause of death could be detected. Blubber samples presenting low lipid concentrations were analysed for persistent organic pollutants. Skin samples were collected for genotyping of the mitochondrial control region. The blubber PCB concentrations were very high [SPCBs, 225 mg/kg lipid weight (lw)], largely exceeding the PCB toxicity thresholds reported for the onset of immunosuppression [9 mg/kg lw ∑PCB] and for severe reproductive impairment [41 mg/kg lw ∑PCB] reported for marine mammals. Additionally, this individual showed equally high concentrations in p,p’-DDE [226 mg/kg lw], PBDEs [5 mg/kg lw] and liver mercury levels [1.1 μg/g dry weight dw]. These results suggest a high placental transfer of pollutants from mother to foetus. Consequently, blubber and plasma PCB concentrations and calf mortality rates are both high in primiparous females. With such high pollutant levels, this neonate had poor prerequisites for survival. The neonate belonged to Ecotype I (generalist feeder) and carried the mitochondrial haplotype 35 present in about 16% of the North Atlantic killer whale from or close to the North Sea. The relevance of this data becomes apparent in the UK West Coast Community, the UK's only residentorca population, which is currently composed of only eight individuals (each four males and females) and no calves have been reported over the last 19 years.Despite worldwide regulations, PCBs persist in the environment and remain a severe concern for killer whale populations, placing calves at high risk due to the mother-offspring PCB-transfer resulting in a high toxicological burden of the neonates.